2021
DOI: 10.1111/aab.12669
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of crown gall in radish (Raphanus sativus L.) inbred lines

Abstract: Studying aberrations of normal developmental processes like plant tumour initiation provides a great opportunity for understanding of systemic control of plant cells differentiation. Most well-studied example of plant tumour is the crown gall caused by Agrobacterium tumefaciens; much less studied are spontaneous tumours developing in plants with certain genotype, regardless of agrobacterial infection. In the present study, we used RNA-seq to analyse the changes in gene expression at the early stages of develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Radish is low in calories and rich in calcium, magnesium, copper, manganese, potassium, vitamin B6, and vitamin C [22]. Radish extract is used to treat several organ disorders [23]. Radish can be used in the treatment of hypertension and carbonic acidosis [24].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radish is low in calories and rich in calcium, magnesium, copper, manganese, potassium, vitamin B6, and vitamin C [22]. Radish extract is used to treat several organ disorders [23]. Radish can be used in the treatment of hypertension and carbonic acidosis [24].…”
Section: Methodsmentioning
confidence: 99%
“…Some scientists found that the iron content of Raphanus sativus leaves is two to three times more than that of the root system. In the research of Hussain, the effect of small magnesium particles and lead on Raphanus sativus was studied in vitro on seed germination and phenological factors [22][23][24]. Analyzing the species Raphanus sativus L., radish and daikon belong to the cabbage family.…”
Section: Methodsmentioning
confidence: 99%
“…The RsSTP expression profiles of different tissues (root, leaf, bolting, flower, silique and callus), their response to heavy metals (cadmium, chromium and lead) and Agrobacterium tumefaciens infection were analysed based on public transcriptome data [ 30 , 54 57 ]. The fragments per kilobase of transcript per million mapped reads (FPKM) data were log 2 transformed, and a heatmap was created using TBtools [ 52 ].…”
Section: Methodsmentioning
confidence: 99%